(untitled) (Journal of KIST Medical College, 2020)
Introduction: Patients leaving against the advice of the treating team before being certified as fit is a major concern and challenge for the treating professionals as it possesses adverse medical outcomes. This study hence aimed at identifying the prevalence and major factors affecting such discharges so that advocacy can be done to help prevent it. Methods: A descriptive cross-sectional study was conducted at emergency department of a tertiary center in Lalitpur from 15th May 2019 to 15th August 2019. All the patients visiting the emergency department were included in the study and a non-probability purposive sampling method was used excluding the patients who denied giving reasons for them leaving against medical advice. Data was collected using pre-structured questionnaire and analyzed using SPSS-v21 software. Results: A hundred and fifteen patients (4.08%) left against medical advice out of 2812 patients who presented to emergency department. There were 63 male patients (54.8%), 75 patients of the total patients in the age group of 15-44 years (65.2%) and those living within a distance of 1km from the hospital (53%). The most common reason for the patients leaving against medical advice was found to be due to financial constraint (38.3%) followed by preference to other hospitals (16.5%). Conclusion: Patients leaving against medical advice possesses a small percentage of actual hospital admissions but is still a major health concern as it drastically increases the morbidity, re-admission rates and total health-care costs. Hence, understanding the general characteristics and predictors of such discharges is of utmost importance to help improve the patient outcome and reduce the health-care costs.